Memories of a gay Catholic boyhood : coming of age in the sixties - D'Emilio, John (Duke University Press, 2022)
"Memories of a Gay Catholic Boyhood is leading queer historian John D'Emilio's memoir about growing up and becoming politically active in the 1960s. Divided into three parts, the book takes you from D'Emilio's childhood in the working-class Bronx to his time spent at a Jesuit high school in Manhattan, and finally to Columbia University, where D'Emilio entered the world of political and social upheaval characterized by the 1960s. Along the way, we read about D'Emilio's first sexual encounters and experiences with gay sexuality. Memories of a Gay Catholic Boyhood sheds light not only on the life of an individual but on the larger baby boom generation whose experiences are still shaping the United States today."--